Propiedades psicométricas de la Nueva Escala de Satisfacción Sexual en estudiantes universitarios - Vásquez-Guevara, Josué Alexis (2025)
Sexual satisfaction is an essential component of general well-being, and its accurate assessment is essential in clinical and research contexts. This study aimed to analyze the psychometric properties of the New Sexual Satisfaction Scale (NSSS) in a sample of Ecuadorian university students. An instrumental approach was used with two independent samples: one of 310 participants for the exploratory factor analysis (EFA) and another of 230 for the confirmatory factor analysis (CFA). The AFE revealed a bifactor structure composed of Intrapersonal Sexual Satisfaction and Interpersonal Sexual Satisfaction, which explained 52.4 % of the total variance. Cross-loaded items were removed to improve the internal validity and structural clarity of the model. The AFC showed acceptable fit indices (CFI= 0.930, TLI= 0.918, RMSEA= 0.0811, SRMR= 0.0442), confirming the validity of the proposed model. The scale presented high internal consistency, with an overall omega coefficient of 0.942. These findings support the factorial validity and reliability of the NSSS in the Ecuadorian university population, evidencing its usefulness as a valid tool for the assessment of sexual satisfaction in Spanish-speaking contexts.